2011
DOI: 10.1002/ejoc.201101198
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Fused 1,4‐ and 1,2‐Dihydropyridines by Domino Reactions of Arylamines, Acetylenedicarboxylate, Aldehydes, and Cyclic 1,3‐Diketones

Abstract: A practical procedure for the preparation of fused 1,4-dihydropyridines was developed through the domino four-component reactions of arylamines, acetylenedicarboxylate, aro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 62 publications
0
15
0
2
Order By: Relevance
“…According to the previously reported reaction conditions for the four‐component reactions containing aromatic aldehydes [6b] and isatins , the four‐component reaction of anilines, dimethyl acetylenedicarboxylate, acenaphthenequinone, and dimedone was carried out in acetic acid at room temperature. Acetic acid was used as both solvent and as acid catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previously reported reaction conditions for the four‐component reactions containing aromatic aldehydes [6b] and isatins , the four‐component reaction of anilines, dimethyl acetylenedicarboxylate, acenaphthenequinone, and dimedone was carried out in acetic acid at room temperature. Acetic acid was used as both solvent and as acid catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we successfully found that the four‐component reaction of anilines, acetylenedicarboxylate, aromatic aldehydes, and cyclic 1,3‐diketones could afford functionalized fused 3,4‐dihydro‐2H‐pyrane, 1,2‐dihydropyridine, and 1,4‐dihydropyridine derivatives under different conditions . When isatins were used to replace aldehyde in this four‐component reaction, the unusual spiro[indoline‐3,2′‐quinolines] were formed in satisfactory yields .…”
Section: Introductionmentioning
confidence: 99%
“…Following the daily increasing requirement on molecular diversity of biologically relevant molecules, developing new MCRs providing 1,4-DHPs containing novel or unprecedented substructures has become an issue of central importance. Later on, Yan and co-workers [27] have established the multicomponent synthesis of different 1,4-DHPs by employing alkynes to incorporate aldehydes, amines and cyanomethylene substrates or cyclic dicarbonyl methylene substrates, [28] respectively. [18][19][20][21][22][23][24][25] However, a disadvantage of enaminone/enaminoester-based MCRs was that enaminones and enaminoesters are not commercially available, prior preparation of enaminones and enaminoesters is required for related synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] A number of domino and multicomponent reactions have been developed by using β-enaminones and β-enamino esters to react further with sequential adding nucleophilic or electrophilic reagents to give versatile heterocyclic systems. [11][12][13][14][15][16][17][18][19][20] Against this background and also in the context of our investigations to develop new domino reactions, herein we report the diastereoselective synthesis of functionalized tetrahydropyrimidin-2-thiones via ZnCl 2 promoted one-pot reactions of cyclic amine, methyl propiolate, aromatic aldehydes and thiourea. [11][12][13][14][15][16][17][18][19][20] Against this background and also in the context of our investigations to develop new domino reactions, herein we report the diastereoselective synthesis of functionalized tetrahydropyrimidin-2-thiones via ZnCl 2 promoted one-pot reactions of cyclic amine, methyl propiolate, aromatic aldehydes and thiourea.…”
Section: Introductionmentioning
confidence: 99%